Internationalization of SME: A systematic Literature Review - Mega Aulianda; S. Sudarmiatin; Hadi Sumarsono (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
The opportunity to enter the international market will encourage SME to experience growth and development. However, SME must also be able to prepare themselves well to compete, survive and thrive in the international market. This research aims to conduct a literature review related to International SME. The method used in this research is the SLR (Systematic Literature Review) method. Data collection is done by documenting all articles that have similar research in the research report. The articles used in this study were 2 international journal articles obtained from the google scholar database. Based on the research obtained results, the supporting factors in the progress of internationalization of SME include Innovation, Balanced Scorecard (BSC), Industry associations, R&D organizations, Customers, Government Policy.